Biological effects of adipocytes in sulfur mustard induced toxicity. (15th January 2018) - Xu, Hua; Gao, Zhongcai; Wang, Peng; Xu, Bin; Zhang, Yajiao; Long, Long; Zong, Cheng; Guo, Lei; Jiang, Weijian; Ye, Qinong; Wang, Lili; Xie, Jianwei
Highlights: Biological effects caused by SM-accumulated adipocytes were studied. Cytotoxicity was compared between SM exposed adipocytes and nonadipocytes. Pathological changes of adipose tissues in exposed rats were examined. Adipokines induced local and systemic inflammation response. Adipose tissue is not only a target but also a modulator in the SM toxicity. Abstract: Sulphur mustard (2, 2′-dichloroethyl sulfide; SM) is a vesicant chemical warfare agent whose mechanism of acute or chronic action is not known with any certainty and to date there is no effective antidote. SM accumulation in adipose tissue (AT) has been originally verified in our previous study. To evaluate the biological effect caused by the presence of abundant SM in adipocyte and assess the biological role of AT in SM poisoning, in vitro and in vivo experiments were performed. High content analysis revealed multi-cytotoxicity in SM exposed cells in a time and dose dependent manner, and adipocytes showed a relative moderate damage compared with non-adipocytes. Cell co-culture model was established and revealed the adverse effect of SM-exposed adipocyte supernatant on the growth of co-cultured cells. The pathological changes in AT from 10 mg/kg SM percutaneously exposed rats were checked and inflammation phenomena were observed. The mRNA and protein levels of inflammation-related adipokines secreted from AT in rats exposed to 1, 3 and 10 mg/kg doses of SM were determined by reverse transcriptase-polymerase chain reaction and enzyme-linked immunosorbent assays. The expressions of proinflammatory and anti-inflammatory adipokines together promoted the inflammation development in the body. The positive correlations between AT and serum adipokine levels were explored, which demonstrated a substantial role of AT in systemic inflammation responding to SM exposure. Thus, AT is not only a target of SM but also a modulator in the SM toxicity.